Directions for Ensuring Financial Stability of Insurance Companies - Shadmanov Khairulla Nasrullaevich (International Journal on Economics, Finance and Sustainable Development, 2022)
The insurance portfolio plays an important role in the activities of any insurance company. Creating a balanced, stable and effective insurance portfolio is a priority for the insurance company. Its principles and functions, theoretical foundations are some of the most pressing issues that researchers are always focused on. In this article we tried to describe in detail what insurance companies should pay attention to when developing an optimal insurance portfolio